Pioneer Work in Opening the Medical Profession to Women - Blackwell, Elizabeth (Rowman & Littlefield Publishers, 2023)
Elizabeth Blackwell (1821-1910) was the first woman awarded the MD degree in the United States. She opened up a small dispensary of her own in a slum district, and in 1859 the now greatly enlarged dispensary was incorporated as the New York Infirmary for Women and Children. By 1868, after consultation with Florence Nightingale, she was able to open up the Woman’s Medical College at the infirmary, which remained in operation for thirty-one years. During the American Civil War she performed valuable service by helping to organize the Woman’s Central Association of Relief, which selected and trained nurses for the war, and the U.S. Sanitary Commission. In 1869, Blackwell moved permanently to England, where she established a successful private practice and was appointed professor of gynecology at the London School of Medicine for Women. She retired in 1907. Pioneer Work in Opening the Medical Profession to Women is the story of Elizabeth Blackwell’s groundbreaking struggle to practice medicine, eloquently told in her own words. Full of insightful reflections on the philosophy of medicine, women's education, the evils of slavery, and the nature of American society in the nineteenth century, this unique autobiography will interest scholars and students of women's studies and the history of science.